An integrated approach towards Sharia compliance e-commerce trust - Ribadu, Mohammed Bashir (Elsevier, 2019)
The Sharia compliance trust concerns over the conventional e-commerce systems among devoted Muslims causes reluctance and abstinence to partake in e-commerce transactions. Although e-commerce trust building mechanisms have been highlighted in the extant literature, there has not been any integrative or exhaustive solution to the Sharia compliance trust concerns of Muslims. Therefore, it became necessary to develop a framework that will provide a guide towards achieving Sharia compliance e-commerce trust (SCE-C). Consequently, relevant literature on e-commerce trust from a conventional perspective and the Sharia perspective were reviewed to gain a background. It provided the basis for proffering a framework for SCE-C trust with a view to enhancing e-commerce adoption and use by Muslims around the world. The framework for SCE-C Trust highlights that e-commerce vendor trustworthiness factors comprising of Sharia compliance, integrity, benevolence, competence, website quality, and third-party assurance if positively moderated by consumer trust propensity and religious commitment will ensure SCE-C trust.